HUBUNGAN ANTARA TINGKAT STRESS DENGAN KEJADIAN PREMENSTRUASI SYNDROME PADA MAHASISWI DI ASRAMA PUTRI STIKES BAHRUL ULUM TAMBAK BERAS JOMBANG - Hartanto, Susiningdiah Sri; Astuti, Wahyu; Nugrahati, Titik; Sutomo, Hadi; Nada, Silfiyah Kitrotun (LPPM STIKes Bahrul Ulum Jombang, 2018)
Woman activity with a higher demands can make a women exhausted of mentally and physically, this will trigger the occurrence of stress. Stress can be raise events premenstruasi syndrome. Such what happened to woman student in a boarding house they experied stress when facing premenstrual syndrome.The purpose of this research was to know the correlation between stress level with incidence of premenstruasi syndrome.This study using analytic design of correlational with delightful cross sectional approach.The population of this research is woman student in a boarding house Stikes Bahrul ‘UlumTambak beras Jombang which totaled 51 college student. Samples have taken from total of 40 student by using purposive sampling techniques.The collection of data using a Student life Stress Inventory (SSI), and Premenstruasi syndrome Evaluation Questioner (PEQ).sutter mild premenstrual syndrome.The result showed almost half of 18 respondents (45,0 %) experienced mild stress light and almost half of the respondents (40,0 %) experienced scene premenstruasi syndrome. The analysis using SPSS test spearman rank (rho)ρ value = 0,000, where the value of ρ value < α(0,05), it means Ha is accepted. The value correlation 0,756 that level of correlation strong. It is expected with this research woman college student can manage a stress level well and increase knowledge of events premenstruasi syndrome.